Penggunaan Wangsalan dalam Sindhenan Karawitan Jawa - Regiana Devi Regiana (PROMUSIKA, 2022)
AbstractThis research was conducted using descriptive analysis research methods on the use of wangsalan in Javanese karawitan sindhenan. Wangsalan in Javanese karawitan functions as a song decoration or gendhing decoration. Wangsalan also has meanings or messages that can be conveyed to listeners, for example, inviting listeners to get rid of doubts in their lives and surrender to God, values of love, values of love for the state, a form of Javanese poetry that contains people's views on life. Java, as well as the requirements for divine teachings, the development of these teachings further takes the form of moral teachings and character. If there is wangsalan, of course there are also perpetrators who bring it. The perpetrator in question is Pesindhen. Sindhen is a woman who can be called a waranggana. Sindhen is someone who sounds wangsalan using a tone or song, and is sung along with gendhing. The form resulting from a mixture of sindhen, wangsalan, and gendhing songs is called sindhenan. Sindhenan is part of the unity with karawitan in order to improve the aesthetic sense or vocals that follow the rhythm of gamelan music with a distinctive voicing technique based on Javanese aesthetic concepts. The purpose of this study is to identify the various forms of wangsalan used in Javanese karawitan sindhenan, the aesthetics contained therein, and the moral message contained in the wangsalan itself.